2014
DOI: 10.1002/asia.201402646
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptide‐Assisted Self‐Assembly of Oligothiophenes: Co‐Assembly and Chirality Transfer

Abstract: The biomolecule-assisted self-assembly of semiconductive molecules has been developed recently for the formation of potential bio-based functional materials. Oligopeptide-assisted self-assembly of oligothiophene through weak intermolecular interactions was investigated; specifically the self-assembly and chirality-transfer behavior of achiral oligothiophenes in the presence of an oligopeptide with a strong tendency to form β-sheets. Two kinds of oligothiophenes without (QT) or with (QTDA) carboxylic groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The parent polythiophene random and block copolymers did not show any well-ordered self-assembled structures (Figure S5), showing that the conjugated backbone itself is not responsible for the selforganization. As we have shown in earlier publications, the presence of an oligopeptide is vital for the self-assembly of oligothiophenes 24,25 and the alternating copolymers. 23 We postulate that the balance between the amount of hydrogen bonding, hydrophobic interaction between the hexyl chains, and π−π interaction is the most important factor that governs the final aggregation state of the hybrid.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The parent polythiophene random and block copolymers did not show any well-ordered self-assembled structures (Figure S5), showing that the conjugated backbone itself is not responsible for the selforganization. As we have shown in earlier publications, the presence of an oligopeptide is vital for the self-assembly of oligothiophenes 24,25 and the alternating copolymers. 23 We postulate that the balance between the amount of hydrogen bonding, hydrophobic interaction between the hexyl chains, and π−π interaction is the most important factor that governs the final aggregation state of the hybrid.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…Synthesis of the Oligopeptide−Polythiophene Conjugates. Our previous studies suggested that N 3 -GVGVOMe is a tetrapeptide that easily forms β-sheets and could be used to adjust the self-assembly behavior of oligothiophenes, 24 and the position of the oligopeptide and its molar ratio toward oligothiophenes strongly influence the outcome of the selfassembly. 25 To further extend the self-assembly study to polythiophenes, the careful balance between the two components should be addressed: the hydrogen bonding makes the polymer prone to dissolving in highly polar solvents, while the π−π stacking between the thiophene rings is more easily broken by less polar solvents such as chloroform and benzene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Here, a peptide-tetrathiophene-peptide (PTP) conjugate (Figure 1) was used as a model object to explore the manipulation of morphology and supramolecular chirality of the assemblies via simply changing the solvent polarity. There are some significant features for PTP: Gly-(L-Val)-Gly-(L-Val) segments at both ends of the thiophene backbone are relatively hydrophilic than the thiophene core and can provide hydrogen bond sites through which β-sheet structures could be formed (Wall et al, 2011; Guo et al, 2013); the thiophene core decorated with two octyls in the middle is a hydrophobic part and can form π-π stacking as well (Lehrman et al, 2012; Guo et al, 2014); the linkers between the thiophene and peptide are flexible and then the spatial location of both hydrophilic and hydrophobic parts in the supramolecular assemblies can be freely tuned under certain conditions. Thus PTP gives chances to tune the self-assembly by verifying the solvent polarity, since H-bonding and π-π stacking are the driving forces for the self-assembly of peptide-thiophene conjugates (Guo et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%